Improvement friction welded 6063-T6 aluminum alloy joint properties - Al Bhadle, Basim M. A.; Hassoni, Safaa M.; Hassan, Kharia Salman (Zielona Góra: Uniwersytet Zielonogórski)
This study aims to investigate the effect of shot peening on the mechanical characteristics and microstructure of an aluminum alloy 6063 friction welded joints. 6063 bars with 12 mm diameters and 70 mm lengths were prepared; some of them were shot peened by steel balls (diameters 1.25 mm) for 15 minutes before the friction welding was carried out on a traditional lathe machine at 1200 rpm. X-ray radiography was used to identify the various internal defects like porosity, concavities, and cracks.
Keywords: friction welding process; aluminum alloys; shot peen; mechanical properties